Highly-ordered wide bandgap materials for quantized anomalous Hall and magnetoelectric effects. (28th April 2017) - Otrokov, M M; Menshchikova, T V; Vergniory, M G; Rusinov, I P; Yu Vyazovskaya, A; Koroteev, Yu M; Bihlmayer, G; Ernst, A; Echenique, P M; Arnau, A; Chulkov, E V
Abstract: An interplay of spin–orbit coupling and intrinsic magnetism is known to give rise to the quantum anomalous Hall and topological magnetoelectric effects under certain conditions. Their realization could open access to low power consumption electronics as well as many fundamental phenomena like image magnetic monopoles, Majorana fermions and others. Unfortunately, being realized very recently, these effects are only accessible at extremely low temperatures and the lack of appropriate materials that would enable the temperature increase is a most severe challenge. Here, we propose a novel material platform with unique combination of properties making it perfectly suitable for the realization of both effects at elevated temperatures. The key element of the computational material design is an extension of a topological insulator (TI) surface by a thin film of ferromagnetic insulator, which is both structurally and compositionally compatible with the TI. Following this proposal we suggest a variety of specific systems and discuss their numerous advantages, in particular wide band gaps with the Fermi level located in the gap.